(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Pricing strategies in the hotel industry are an integral part of overall hospitality management. They are designed to help make sure the hotel gets the maximum revenue it can, while also ensuring customer satisfaction stays high